Instagram como instrumento de Divulgação Científica para a Biologia - Pereira, Gabriele Cristina Catosso (Universidade Federal de São Carlos, 2021)
The work developed is based on the premise of the intense interaction of young people through social networks verified in today's reality, and from there proposes to investigate possibilities of this media space for education, directing its focus to Instagram, a social network much used today among young people, and at the same time the one with less jobs academics with a focus on Education or the dissemination of science. It can be said that the social networks, in particular, is a topic that there is a lot of investment in research today, it can also consider that a large part of the Brazilian (and worldwide) population has access to them. So, why not use them, in favor of science and turn it into an instrument for scientific dissemination? The methodology for the development of the project involves the creation of a Profile, production of images, posting of these in the feed and in the stories, were questions and polls were created with the aim of encouraging followers to interact - in where elements were obtained for analysis of the posted material. This work explores powers of Instagram as a tool for Scientific Dissemination for Biology.
Instagram as a tool for Scientific Dissemination for Biology
Instagram como herramienta de divulgación científica para biología
Keywords: Ensino de biologia; Divulgação Científica; Artrópodes; Instagram; Biology teaching; Scientific Dissemination; Arthropods; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO